2008
DOI: 10.1161/strokeaha.107.505727
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Clinical Safety Study of Sonothrombolysis Augmentation With Ultrasound-Activated Perflutren-Lipid Microspheres for Acute Ischemic Stroke

Abstract: Background and Purpose-Ultrasound transiently expands perflutren-lipid microspheres (S), transmitting energy momentum to surrounding fluids. We report a pilot safety/feasibility study of ultrasound-activated S with systemic tissue plasminogen activator (tPA). Methods-Stroke subjects treated within 3 hours had abnormal Thrombolysis in Brain Ischemia (TIBI) residual flow grades 0 to 3 before tPA on transcranial Doppler (TCD). Randomization included Controls (tPAϩTCD) or Target (tPAϩTCDϩ2.8 mL S). The primary saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 22 publications
3
118
0
2
Order By: Relevance
“…40 Several published studies have used different commercially available microspheres (TABLE 1). [43][44][45][46] Molina et al 43 pioneered this approach in stroke patients and reported the largest study to date that compared the CLOTBUST Target arm to the CLOTBUST Target insonation protocol (2 MHz continuous TCD-monitoring) combined with Levovist air microspheres (Schering, Berlin, Germany). Investigators demonstrated that at 2 hours after TPA bolus the TPA ϩ TCD ϩ Levovist group achieved a 55% sustained recanalization rate, compared with 38% in the TPA ϩ TCD group of the CLOTBUST trial.…”
Section: Microsphere-potentiated Ultrasound-enhanced Thrombolysismentioning
confidence: 99%
“…40 Several published studies have used different commercially available microspheres (TABLE 1). [43][44][45][46] Molina et al 43 pioneered this approach in stroke patients and reported the largest study to date that compared the CLOTBUST Target arm to the CLOTBUST Target insonation protocol (2 MHz continuous TCD-monitoring) combined with Levovist air microspheres (Schering, Berlin, Germany). Investigators demonstrated that at 2 hours after TPA bolus the TPA ϩ TCD ϩ Levovist group achieved a 55% sustained recanalization rate, compared with 38% in the TPA ϩ TCD group of the CLOTBUST trial.…”
Section: Microsphere-potentiated Ultrasound-enhanced Thrombolysismentioning
confidence: 99%
“…3,4,15,16,20,23 Two studies were excluded (one consisted of a pilot study with 3 patients in the control arm, 3 and the other was published as an abstract 20 ). We did not find any randomized study addressing the effects of low-frequency transcranial ultrasound on thrombolysis.…”
Section: Resultsmentioning
confidence: 99%
“…17 In addition, 2-MHz ultrasound waves enhance tPA-thrombus dissolution by fluid streaming around the clot surface and disaggregation of fibrin fibers, which results in a greater amount of binding sites for tPA without heating or cavitation. 3 In stroke patients treated with tPA, intravenous infusion of microbubbles or microspheres has been proved to accelerate clot lysis during 2-MHz ultrasound monitoring, by transmitting energy momentum from an ultrasound wave to residual flow. 3,11,12,22,23 These mechanisms support the findings of sonothrombolysis in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Augmentation of systemic tPA treatment can be accomplished with low power ultrasound and gaseous microspheres [39][40][41][42][43][44]. Since human application of frequencies below diagnostic range (i.e.…”
Section: Novel Experimental Approachesmentioning
confidence: 99%
“…Molina et al pioneered the use of gaseous microspheres in combination with CLOTBUST monitoring methods and reported safety and recanalization rates with the first generation air-filled microspheres (Levovist, Schering AG) as well as newer diagnostic microspheres (Sonoview, Bracco) [39,41]. These microspheres were designed for diagnostic purposes to be given as boluses in order to enhance returned echoes and improve quality of ultrasound images.…”
Section: Novel Experimental Approachesmentioning
confidence: 99%